Kecerdasan Emosi, Kecerdasan Spiritual dan Perilaku Prososial Remaja - Yantiek, Ermi (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2014)
Abstract.Â Purpose of this study is to determine a relationship between emotional intelligence and spiritual intelligence with pro social behaviour of adolescents. The research sample are students of SMA N 1 Gresik which amount is 124 people using purposive random sampling technique. Data analysis and regretion analysis are obtainable from the results count in the amount of 9.667 with p<0,01 (p = 0,000), which means there are significants relationship between emotional quotions with pro social behaviour of adolescents; data analysis of spiritual intelligence variabel with pro social behaviour of adolescents are obtainable from t counts > t table with p = -2,754 (p<0,01) that means there there are significants relationship between spiritual quotions with pro social behaviour of adolescents. Percentage of emotional intelligence and spiritual intelligenceâ€™s effective donation with pro social behaviour of adolescents are 72, 3 %.Keyword: Emotional Quotient (EQ), Spiritual Quotient (SQ), Pro social behaviour of adolescents